Senna reticulata (Willd.) H. S. Irwin & Barneby (Fabaceae) AS “PASTURE KILLER” (“MATAPASTO”) PIONEER TREE IN AMAZONIAN FLOODPLAINS - Parolin, Pia (2016)
Senna reticulata (Willd.) H. S. Irwin & Barneby (Fabaceae) is a pioneer tree which colonizes open areas in Amazonian floodplains. It is very abundant throughout Amazonia along the nutrientrich whitewater rivers, and can be considered to be one of the most efficient colonizers of open areas. It possesses a very high tolerance towards flooding of the roots and stem, and performs extremely high photosynthetic assimilation and fast growth despite prolonged waterlogging. Efficient seed dispersal and the ability of resprouting after a period of unfavourable conditions add to its effectiveness. These features led the local people to consider Senna reticulata a noxious woody weed called ‘matapasto’ (“pasture killer”) although in the successional sequence it represents a short-lived woody stage which enhances the establishment of highly diverse forests.